Implementasi Pembiasaan Karakter Religius di SDN 06 Koto Baru Kabupaten Dharmasraya - Qasasi, Hisnatul (Lembaga Yasin AlSys, 2024)
There are character values that are ignored in student character development. These characters are now starting to fade because it is difficult to develop character through learning. Apart from that, there are still many people who lack confidence in instilling character education values such as good manners and good manners in children, and as time goes by, students' character is getting worse day by day. This happened at SDN 06 Koto Baru, Dharmasraya Regency, not much different from the incident described. So, it became the researcher's interest to discuss the habit of religious character education and it was found that there were Duha prayer activities, Friday Kultum and Infaq. The method used in this research is a qualitative method with case studies. The research instruments used are primary data and secondary data. The data collection techniques used were interviews and observation. Meanwhile, the data analysis used is data collection, data reduction, data presentation, and drawing conclusions. So, the implementation of religious character education through routine habituation at SDN 06 Koto Baru is carried out through routine habituation activities consisting of congregational Dhuha prayers, Friday Kultum and Friday Infaq, with students and their guardians so that religious values, discipline and responsibility are created.